PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN SUASANA KEAGAMAAN - Mahpudin; Tamyis; Rahmat Hidayat (UNISAN JURNAL, 2025)
The teacher is an important component in education. Teachers are involved in increasing faith and creating a religious atmosphere in the school environment. Given the current developments in globalization and information, it is increasingly concerning, as there are many negative things that need to be avoided and complaints from parents about children who are difficult to manage. and often ignore their parents even more concerned with playing than learning. This study uses a qualitative approach with descriptive methods. Data collection techniques using interviews, observation, documentation. Informants were determined through a purposive sampling technique. The analysis that the writer uses is triangulation. The results showed that the Islamic religious education teacher at SD Negeri I Warunggunung Lebak had carried out his role as a teacher, as an educator, as a motivator, as a role model, as a facilitator, as an evaluator and at the same time as a leader in increasing the religious atmosphere but the religious atmosphere had not been created optimally